2019
DOI: 10.1038/s41598-019-56192-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of agro-morphological variability of dry-season sorghum cultivars in Chad as novel sources of drought tolerance

Abstract: Dry-season sorghum is a type of sorghum whose establishment ends at the end of the rainy season and its development takes place during the dry and cold harmattan period. Its root system is particularly well developed with deep penetration for water withdrawal. This study was conducted to assess the level of genetic diversity present among dry-season sorghum in Chad’s Sudanese zone using phenotypic traits, and to identify new sources of drought tolerance that could be used in sorghum breeding programs. A high v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 12 publications
4
32
1
Order By: Relevance
“…Generally, the 0.5 t ha −1 average grain yield production in this study was quite low compared to the average 1.0 t ha −1 observed in Chadian grain sorghums or 0.87 t ha −1 for dry-season grain sorghum in the same region 14 . According to 7 , sweet sorghum is characterized by reduced grain yield as compared to grain sorghum.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Generally, the 0.5 t ha −1 average grain yield production in this study was quite low compared to the average 1.0 t ha −1 observed in Chadian grain sorghums or 0.87 t ha −1 for dry-season grain sorghum in the same region 14 . According to 7 , sweet sorghum is characterized by reduced grain yield as compared to grain sorghum.…”
Section: Discussioncontrasting
confidence: 72%
“…However, our study showed that some white midrib accessions were very juicy. The sweet sorghum accessions from the Sudanese zone were identified to be from the caudatum and bicolor race, unlike the dryseason sorghum which are from the durra race 14 . According to 28 , sweet sorghum belongs to bicolor, caudatum, durra and hybrid bicolor-guinea race.…”
Section: Discussionmentioning
confidence: 96%
“…The phenotypic and genotypic coefficient calculated for 12 quantitative traits were listed in table 2. The high GCV and PCV value was observed for plant height upto flag leaf, flower length with pedicle, time of panicle emergence (Subramanian et al 2019), total height (Naoura et al 2019;Subramanian et al 2019), panicle length without peduncle (Karadi and Kajjidoni, 2019;Naoura et al 2019), panicle branch length, panicle neck length (Naoura et al 2019), thousand grains weight (Mofokeng et al2019) and single plant yield (Swamy et al 2018;Subramanian et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…It was also noted that hundred seed weight was low in 2019 as compared to 2018. Similar studies were also performed by various researchers to characterize and evaluate a wide range of crops including lentil 3,7,11,[14][15][16][17][18] .…”
Section: Discussionmentioning
confidence: 94%
“…Assessment of genetic diversity based on phenotypic markers has been conducted worldwide in the near past in lentil and other legumes 3,7,11,[14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%